Arthroscopic All-Inside Posterior Cruciate Ligament Avulsion Fracture Suture Fixation With Double-Tunnel Pullout and High-Strength Suture Tape Augmentation Using Trans-septal Approach - Marcello Capella, M.D.; Davide D’Antonio, M.D.; Luca Drocco, M.D.; Luca Barberis, M.D.; Daniele Vezza, M.D.; Fortunato Giustra, M.D.; Alessandro Massè, M.D. (Arthroscopy Techniques)
This technical note aims to provide a detailed description of our arthroscopic technique for suture fixation of posterior cruciate ligament (PCL) tibial avulsion fractures. Various surgical approaches have been described, including both open and arthroscopic techniques. The arthroscopic approach can be less disruptive and more accurate in visualizing anatomic landmarks. It also may ensure good and reliable fracture reduction and fixation. This article describes a technique for arthroscopic all-inside fixation of PCL avulsion fractures using a double-tunnel pullout method. The procedure involves trans-septal visualization and whipstitching suturing of the PCL with 1.5-mm high-strength, nonresorbable transverse ribbon suture (LabralTape; Arthrex, Naples, FL) and a crosstie-like suture with a high-strength, nonresorbable suture tape (FiberTape; Arthrex) embracing the PCL from anterior to posterior. Finally, the avulsion fracture is secured by tensioning a high-strength suture tape from the femur to the tibia along the PCL structure as an InternalBrace ligament augmentation (Arthrex). This technique allows for anatomic reduction and stable fixation of the displaced fracture through optimal trans-septal visualization and the PCL whipstitching technique, further secured by the InternalBrace ligament augmentation, enabling early and intensive rehabilitation.